Music listening in everyday life: Devices, selection methods, and digital technology - Krause, Amanda; north, A. (2015)
Two studies considered whether psychological variables could predict everyday music listening practices more than those demographic and technology-related variables studied predominantly hitherto. Study 1 focused on music-listening devices, while Study 2 focused on music selection strategies (e.g. playlists). Study 1 indicated the existence of a one-dimensional identity based on music technology. Further, psychological variables (such as innovativeness and self-efficacy) predicted whether individuals possess such an identity. Moreover, while psychological variables predicted whether individuals preferred ‘familiarized’ advantages inherent to listening devices, a preference for ‘progressive’ advantages was predicted by technological behaviors. Study 2 supported the first study in terms of identity, and demonstrated that a different pattern of variables predicted playlist listening from listening to music via shuffle. More generally, the findings suggest the utility of applying constructs from consumer psychology to everyday music-listening behaviors.